Vaccination through time: from the first smallpox vaccine to current vaccination campaigns against the COVID-19 pandemic - Conti, Andrea Alberto (Acta Biomedica Atenei Parmensis, 2021)
The systematic study of the evolution of the concept of vaccination constitutes a fascinating journey through time and the scientific development of effective and safe vaccines against infectious diseases is one of the greatest achievements in the history of medicine. In the western world vaccination dates back to the eighteenth century, a period in which smallpox was a diffused and often lethal disorder, and in many countries attempts at the prevention of such a medical and social threat were conducted. The English surgeon Edward Jenner (1749-1823) is commonly considered the discoverer of the vaccination for smallpox.Moving from remote history to recent periods, the ongoing 2019-2021 coronavirus disease (COVID-19) pandemic has posed a tremendous challenge to the health systems and consequently to entire society of the countries involved. It has triggered all over the world the rapid development of several effective vaccines, never before prepared in such a brief span of time. It must be acknowledged that modern vaccinology as a science stands at the crossroads of multiple medical specialities and scientific disciplines, being in particular debtor to health care branches born and developed between the end of the nineteenth century (infectivology) and the beginning of the twentieth (immunology). In turn, twentieth century explosive progress in the field of vaccination has triggered the development of other important medical areas, from immunopathology to infectious diseases therapy, and from prevention to anti-cancer treatment.Nowadays, effective and diffused control of infectious diseases cannot do without  the presence of vaccines, as the COVID-19 pandemic has once again demonstrated, and the role of well structured vaccine programs and of capillary and systematic vaccine campaigns has become central not only for the health but also for the existence itself of entire populations all over the world.